UrsaNav: the power of the bear. Issue 6 (30th March 2019) - White, Susan; Hallows, Karen
Abstract : Theoretical basis: Students will need to know basic capital budgeting techniques to value UrsaNav and its divisions. Students must determine which cash flows are relevant and determine an appropriate return on investment. Some of the issues that need to be addressed include: how to handle taxes in a discounted cash flow analysis when valuing an S Corp. where incentives depend on current (known) tax provisions and future (unknown) tax provisions; how to use comparable multiples to develop a cost of capital for a DCF valuation; and how to value a firm using comparable transactions. Research methodology: Case information was obtained through interviews with the owner, Charles Schue. In addition, the authors researched industry and comparable company data, along with current events relating to government consulting. Case overview/synopsis: UrsaNav is a US-based, international provider of advanced engineering and information management consulting services in the naval navigation industry. After about a decade of operating and growing, the firm had become successfully diversified; however, it had also grown too large to manage effectively. Thus, the company was spun-off into three separate segments: Tagence, Geodesicx and UrsaNav. These segments went "back to the basics, " and focused more on serving customers, with each having a more defined company focus. Is this a move that creates or destroys value? How could it create value for the firms' founders? Complexity academic level: This case is intended for an advanced undergraduate or an MBA corporate finance class or an entrepreneurship elective. Students interested in analyzing whether or not decision makers within a company would want to spin-off divisions, or merge with another company, or divest a company would find this case appealing. Other students who just want to analyze whether the company has grown too much would be good candidates to do this case.